Synthesis and evaluation of anticorrosion properties of onion mesocarp-nickel nanocomposites on X80 steel in acidic cleaning solution - Ekemini Ituen; Ambrish Singh; Lin Yuanhua; Ruiyun Li (Journal of Materials Research and Technology, 2020)
New Ni-nanocomposites were synthesized from waste onion mesocarp extracts and characterized by UV-Vis, FTIR, XRD, SEM/EDS, DLS and TEM techniques. Monodispersed non-agglomerating colloidal nanoparticles with spherical shape and particle sizes of 30–50 nm were obtained. The nanocomposites (Ni-OMNPs) exhibit O, N and CC sites which facilitated their physisorption on X80 steel surface from aqueous 1 M HCl and efficient protection of the steel surface against corrosion in the acid solution. Ni-OMNPs inhibits X80 steel corrosion in 1 M HCl with 93.99 ± 2.10 % efficiency at 30 °C and reduces surface pitting and roughness by 51.2 % and 52.3 % respectively. AFM, SEM, EDAX and FTIR techniques were used to check extent of surface protection and inhibitor-steel interaction mechanism. Compared to crude extract feedstock, Ni-OMNPs show higher corrosion inhibition and resistance to thermal and biochemical degradation. Unlike the crude extract, inhibition efficiency of Ni-OMNPs did not change considerably throughout 150 days of storage at different temperatures.